Toxoplasma gondii infection in patients with schizophrenia - Bakre, Hawre M.; Hussain, Saeed K.; Ali, Sirwan K. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and Objectives: Schizophrenia is a complex chronic neuropsychiatric disease of the central nervous system, believed to have multiple etiologies. Toxoplasma gondii has emerged as an interesting candidate as a possible cause of some cases of schizophrenia. As there is scarce information about the seroprevalence of T. gondii infection in psychiatric patients in Erbil; we investigated the seroprevalence of T.gondii in schizophrenic patients and compared with that obtained from control individuals in Erbil correlated with inflammatory marker C-reactive protein.Method: This case control study included 93 schizophrenic patients seeking medical advice at Hawler Psychiatric Hospital and private clinics with 93 non psychiatric control were screened for the presence of anti-toxoplasma IgG, IgM (by ELISA test) and C-reactive protein using qualitative methods. A questionnaire was used to collect socio-demographic and behavioral data among the respondents.Results: In chronic cases anti-Toxoplasma gondii IgG antibodies were seropositive in 30/93 (32.3%) of the schizophrenic patients and 4/93(4.3%) of control (P <0.001). The seropositive rate of IgM antibodies was 9.7% and 1.1% among schizophrenic patients and control, respectively (P = 0.006). The result of C-reactive protein positivity among patients and control was 23.6% and 3.22%, respectively (P <0.001).Conclusion: Our results delineate that association might exist between Toxoplasma gondii infection and schizophrenia etiology